THE ROLE OF TAX STRATEGY IN ACHIEVING CORPORATE SUSTAINABILITY: EMPIRICAL EVIDENCE FROM INDONESIAN PUBLIC COMPANIES - Mirza Maulinarhadi Ranatarisza; Aisyafarras Alfianida (Universitas Airlangga, 2026)
This study examines how corporate tax strategies influence financial performance among publicly listed companies in Indonesia. Two distinct dimensions of tax strategy are investigated. The first is Minimalization Tax Strategies, which focus on short-term tax burden reduction. The second is Sustainable Tax Strategies, which emphasize consistency in tax planning over time as a means of supporting long-term business sustainability. The analysis incorporates profit margin, firm solvency, and stock valuation as control variables to isolate the effects of tax strategies on financial outcomes. Employing a quantitative approach, the study draws on data from companies listed on the Indonesia Stock Exchange. The findings reveal that Sustainable Tax Strategies exert a positive and significant effect on financial performance. Minimalization Tax Strategies, by contrast, demonstrate no significant impact on financial performance despite their potential to enhance short-term profitability. This outcome likely reflects the risks that aggressive tax reduction poses to business continuity over time. These results contribute to the theoretical discourse on financial sustainability and agency theory. From a practical standpoint, the findings offer insights for corporate managers and regulators who seek to align tax planning practices with broader sustainability objectives.